Pengaruh Penambahan Serat Ampas Tebu Terhadap Sifat Mekanik Pada Campuran Beton Normal - Kampati, Tri Budi; Djauhari, Zulfikar; Suryanita, Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bagasse is a waste material and the use of this material for construction is still limiterd. In this study, fiber extracted from bagasse was used in teh concrete. This research aimed to examine the mechanical properties of concrete, namely compressive strength, bending strength and split tensile strength. The percentage of bagasse fiber used was 0.3%, 0.5% and 0.7% of the weight of coarse aggregate. Compresive strength was tested on the age 7 days, 14 days, and 28 days, while the flexural strength and split tensile strength were tested on the age of 28 days. Workability test conducted on specimens contained 0.3%, 0.5%, and 0.7% of bagasse showed the volume of slump at 8 cm, 6.5 cm and 4.5 cm. In testing the compressive strength of concrete, the highest value was produced from normal concrete which was 22.92 MPa.The value of flexural strength of concrete increased by 9.47% from the normal flexural strength of concrete with the addition of 0.5% bagasse at 4.45 MPa. Different with the value of concrete split tensile strength, the highest value was obtained in the addition of 0.3% bagasse, which was 2.21 MPa with an increase of 19.48% of normal concrete. This research concluded that the addition of bagasse fiber can reduce workability.On compressive strength testing with the addition of bagasse fiber, the compressive strength was lower than that of normal concrete but still within the range of concrete plan quality 17 MPa. Addition of bagasse fiber to the concrete mixture could increase the flexural strength by 0.5% and split tensile strength by 0.3%.With the addition of bagasse fiber to concrete, it is hoped that bagasse waste can be utilized and concrete quality is achieved Keywords: Fiber Concrete, Bagasse Fiber, Split Tensile Strength, Flexural Strength, Compressive Strength